AGENT AND EXPERIENCER IN PUDARNYA PESONA CLEOPATRA NOVEL BY HABIBURRAHMAN EL SHIRAZY: A STUDY OF SEMANTIC ROLE - R. Myrna Nur Sakinah; Khaerunnisa Siti Latifah; Jenny Rahmi Nuraeni (Universitas Islam Negeri Sunan Gunung Djati, 2020)
This research purposes at describing the roles of semantic study precisely the roles of agent and experiencer in Pudarnya Pesona Cleopatra novel written by Habiburrahman El Shirazy. The research conducted by the writer is qualitative research. The data of this study are agent and experiencer roles that the data source is taken from Pudarnya Pesona Cleopatra novel written by Habiburrahman El Shirazy published in 2003. The method that is used by the writer to collect the data is documentation with the steps: (1) figure out the sentences that contain agent and experiencer in that novel, (2) classify the types of sentences by investigating the novel. In analyzing data, the writer used Saeed’s theory of participant roles for the major theory. The result of this study shows that there are seventeen patterns that are classified into two roles. They are ten sentences of the agent and seven sentences of the experiencer.Keywords: Semantic, Participant Roles, Agent, Experiencer